Efficacy of Yoga Asana and Gym Ball Exercises in the management of primary dysmenorrhea: A single-blind, two group, pretest-posttest, randomized controlled trial - Veena Kirthika S; K Padmanabhan; Selvaraj Sudhakar; S Aravind; C R Praveen Kumar; S Monika (Wolters Kluwer Medknow Publications, 2018)
Background: Primary dysmenorrhea (PD) is characterized by cramping lower abdomen pain that may radiate to the lower back and upper thigh and commonly associated with stress, headache, and diarrhea, and thereby decreases the quality of life. It occupies 20%-90% of the female population in reproductive age. Many conservative treatment methods such as yoga asana, physiotherapy through gym ball/therapy ball/Swiss ball exercises, etc., are available to treat them. More efficient among them is not known. Purpose: The aim is to compare the efficacy of yoga asana and gym ball/therapy ball/Swiss ball exercises in the management of female with PD. Methodology: A total of 30 female with PD were recruited by the simple random sampling to participate in this two group pretest-posttest, single-blinded randomized clinical study. Recruited female with PD were randomly allocated into two groups, Group A and Group B. Group A were provided with yoga asana for 60 s duration × 5 repetition/session/day × 3 days/week × 12 weeks. While Group B received set of gym ball exercises for 10 s hold ×12 times/set × 3 sets/day × 3 days/week × 12 weeks. Level of menstrual distress (MOOS Menstrual Distress Questionnaire [MDQ]) and pain scores (visual analog score ([VAS]) were documented at baseline and 12th week after intervention and analyzed. Results: Group B demonstrated significance difference (P < 0.05) in MDQ and VAS when compared to Group A. Conclusion: Twelve-week gym ball exercises have the sufficient potential to decrease level of menstrual distress and related pain among female with PD when compared to yoga asanas.